(3TYH GdEjeGfs - (3YHO GdLdjd Hf ehSi GdbUQj, CHh eMeO,J (B608 (3g` s
(3ChdgG (B:s
(3GdTYHI GdChdi TgGOI Cf dG Edg Gddg GdTYHI GdKGfjI GdEbQGQ HCf eMeOkG QShd Gddg Gddg s
(3BNQgG (B:s
(3hgcPG LejY GdCHhGH eKd HGH GdcSH GdLGeY dCHhGH GdMdGd hGdMQGe hGdMQGe LGeY deMQeGJ GdLhGQM GdSHYI Ydi ENJdGagG hZjQ Pdc ef GdCHhGH JeJ GdTYH s
(3GdfSNI HgG MhGTs
(3GdhQbGJ GdYTQ GdChdi hGdKdGK GdCNjQI efgG cJHJ HNW fSNi MOjKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B276s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs